Relevansi Khilāfah, Imāmah, Imārah, dan Salṭanah dalam Sistem Pemerintahan Islam Kontemporer: Kajian Tafsir Tematik - Setyarama, Handri; Erdiansah, Fandi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2024)
This article aims to explain how the mufassir’s interpretation of the Qur’anic verses that indicate about the style or system of government in khilafah, imamah, imārah and salṭānah term and how its relevance to the Islamic government system today. The method used is descriptive-analytical method as commonly applied in qualitative research models. This article shows that (1) from the identification of Qur’anic verses that indicate the concept of government system as many as 26 verses, the word khalīfah is more often used by Allah for the meaning of government and ruler. (2) in the Qur'an, terms such as khalīfah, imām, ulū al-amr, and sulṭān refer to the concepts of leadership and governance without specifying a particular form of state or system of government that Muslims must follow. (3) by adhering to the principles of Sharia, Islam allows for various flexible forms of government to reflect national sovereignty and the welfare of the community, without being bound to any specific system.